ВИБІР ПЕРІОДУ ДИСКРЕТИЗАЦІЇЇ ЦИФРОВИХ РЕГУЛЯТОРІВ ПРОМИСЛОВИХ ЕЛЕКТРОПРИВОДІВ - Шуруб, Ю.В.; Цицюрський, Ю.Л. (Інститут електродинаміки Національної академії наук України, 2025)
The paper is devoted to the analysis of the influence of the method of determining the permissible sampling period in digital controllers of automatic control systems of industrial electric drives on their quality indicators. The possibility of determining the permissible sampling period based on the frequency of the bandwidth of the amplitude-frequency characteristic of both the open and the closed system was studied. It is shown that the use of the bandwidth of an open system to determine the permissible sampling period does not allow taking into account such properties of the control object as delay and astaticity. These are quantitative recommendations for determining the bandwidth of a closed system for determining the permissible sampling period of digital controllers of industrial electric drives. Ref. 13, fig. 12.